Functionality and Storability of Cookies Fortified at the Industrial Scale with up to 75% of Apple Pomace Flour Produced by Dehydration - Zlatanović, Snežana (Foods, 2019)
Apple pomace flour (APF) with high content of dietary fibers (DF), total polyphenolics (TPCs) and flavonoids (TFCs) was produced at the industrial scale. Bulk and tapped density, swelling, water and oil holding capacity, solubility and hydration density of fine and coarse APF with average particle size 0.16 and 0.50 mm were compared. The effect of wheat flour substitution with 25%, 50% and 75% of fine and coarse APF was studied upon cookies production at the industrial scale and after one year of storage. Coarse APF performed better in respect to sensorial properties, content and retention of dietary compounds and antioxidant (AO) activity. The cookies with optimal share of coarse APF (50%) contained 21 g/100 g of DF and several times higher TPC, TFC as well as AO activity than control cookies, retained well health promoting compounds and maintained an intensely fruity aroma and crispy texture. They were acceptable for consumers according to the hedonic test.